Keasaman Cairan Tubuh dan Rasio Kelamin Anak Domba Garut (Ovis aries) yang Diberi Kation-Anion Ransum yang Berbeda - F Fathul; T Toharmat; I G Permana; A Boediono (Faculty of Animal Science, Bogor Agricultural University, 2008)
The objective of this research was to determine the effects of dietary cation-anion difference (DCAD) on acidity of ration, blood, vaginal mucous, and urine, number of fetus, number of offspring, and offspring sex ratio. The treatments were rations with DCAD -28, -18, 0, +14, and +32 meq which were offered to 15 ewes. This research used randomized complete block design. There were three groups, (I) ewes previously had twin female offsprings; (II) ewes previously had twin male offsprings; and (III) ewes previously had twin male and female offsprings. Results of this study showed that there were no differences observed for blood's pH, vaginal liquid's pH, offspring number, and offspring sex ratio. Increasing DCAD affected ration's pH, urine's pH, and number of fetus for each ewe. Blood's acidity was not affected by DCAD, but DCAD -28 meq reduced acid of blood, metabolic acidosis, and urine; the number of fetus and offspring. DCAD -28 meq might be anions excessive in the ration. DCAD 0 meq was relatively the best of ration because gave the normality of blood, metabolic, and urine, also relatively the highest of fetus and offspring. The offspring sex ratio related to vaginal mucose pH when artificial insemination was applied (r= 0.75) and ration's pH (r=0.47). Ewes previously had twin female lambs gave the number of fetus and offspring sex ratio were 2.00+0.71 and 0%, respectively. Ewes previously had twin male lambs gave the number of fetus and offspring sex ratio were 2.80+1.30 and 15.00+8.50%, respectively. Ewes previously had twin male and female lambs gave the number of fetus and offspring sex ratio were 1.60+1.14 and 61.75+31.50%, respectively.Key words: DCAD, pH, offspring sex ratio, lamb, ewe